2017
DOI: 10.1007/s11130-017-0627-0
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Current Status and Future Prospects of Winged Bean (Psophocarpus tetragonolobus) in Tropical Agriculture

Abstract: Winged bean, Psophocarpus tetragonolobus (L.) DC., is analogous to soybean in yield and nutritional quality, proving a valuable alternative to soybean in tropical regions of the world. The presence of anti-nutritional factors and high costs associated with indeterminate plant habit have been major concerns in this crop. But occurrence of good genetic variability in germplasm collections offers precious resources for winged bean breeding. However, lack of germplasm characterization is hindering such efforts. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 53 publications
2
36
0
Order By: Relevance
“…ese figures are higher than that reported by Singh et al [18], who recorded a crude fat content of 0.47% in the fully mature seeds. ey are however similar to those of previous studies that reported [15][16][17][18][19][20].4% [19] and those of other legumes such as chickpea (5.76-6.87%) as reported by Boye et al [20]. e result obtained for the tubers (Table 5) ranged from 0.21 (Tpt16) to 4.53 (Tpt33).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…ese figures are higher than that reported by Singh et al [18], who recorded a crude fat content of 0.47% in the fully mature seeds. ey are however similar to those of previous studies that reported [15][16][17][18][19][20].4% [19] and those of other legumes such as chickpea (5.76-6.87%) as reported by Boye et al [20]. e result obtained for the tubers (Table 5) ranged from 0.21 (Tpt16) to 4.53 (Tpt33).…”
Section: Discussionsupporting
confidence: 91%
“…Considering that most of these ANFs are destroyed by boiling or autoclaving [34], properly processed winged bean can be safely used as a major plant protein source. Overall, the proximate and antinutritional assessments of winged bean seeds and tubers were similar to those of previous studies of the crop and other similar crops [12,19,21,[44][45][46][47].…”
Section: Discussionsupporting
confidence: 83%
“…Zhang (2015) had previously recommended polar solvent, in particular, methanol to extract condensed tannin from walnuts green husk. For P. tetragonolobus , n ‐hexane yielded the highest tannin content, probably due to the formation of saturated fatty acid–tannin complexes which facilitated tannin extraction by non‐polar solvent (Lepcha, Egan, Doyle, & Sathyanarayana, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Its ability to produce green pods, edible leaves, and tuberous roots makes it a useful horticultural crop. Its mature seeds are a good source of protein and other nutrients, making winged bean a potential pulse crop for large-scale production in the humid and sub-humid tropics (NAS 1975b;Gross 1983;Kadam et al 1984;Misra and Misra 1985;Lepcha et al 2017). The nutritional profile of these edible parts could play a major role in diet improvement of people especially in areas where major vegetable crops require high-inputs, limiting consumers' access to vegetables.…”
Section: Winged Bean: a Perspectivementioning
confidence: 99%
“…Protein content and fatty acid profiles compare favourably with soybean and chickpea (Cicer arietinum) (Claydon 1975;Kadam et al 1984), and peanut (Garcia et al 1979;Ekpenyong and Borchers 1980a;Garcia and Palmer 1980). A comprehensive assessment of the nutritional properties of winged bean seeds and the other edible parts, along with comparisons with other leguminous crops, have being adequately reviewed elsewhere (see for example Claydon 1975Claydon , 1983Kailasapathy and Sandrasegaram 1983;Kadam et al 1984;Kantha and Erdman 1984;Kailasapathy and Macneil 1985;Prakash et al 1991;Lepcha et al 2017). However, for mature seeds, two points should be mentioned.…”
Section: Mature Seeds Consumptionmentioning
confidence: 99%